PELAKSANAANPEMBELAJARAN KETERAMPILAN BERBICARA DI SMA ADABIAH PADANG - Susetri, Indah; Atmazaki, Atmazaki (Universitas Negeri Padang, 2020)
ABSTRACT This study aims to describe the implementation of learning speaking skills in class XII Natural Sciences Adabiah Padang. In this study, the implementation of learning includes three main components, namely: (1) learning material for speaking class XII SMA Adabiah Padang, (2) learning methods of speaking class XII SMA Adabiah Padang, and (3) evaluating speaking learning class XII SMA Adabiah Padang. This type of research is a qualitative research with descriptive methods. This research was conducted in the SMA Adabiah Padang. The data in this study were observation, interviews, and study documentation about the understanding and implementation of learning speaking skills conducted by Indonesian language teachers at SMA Adabiah Padang, which were obtained from data sources. The techniques used are observation, interviews, and documentation studies. Techniques used to analyze data are data identification, data presentation, and drawing conclusions. Based on the research findings and research results, the following three things can be concluded. (1) The use of learning materials in SMA Adabiah Padang has implemented learning materials with excellent categories. Teaching material is selected and determined with consideration and attention to problems, including (a) the objectives to be achieved to be relevant, (b) the level of students' thinking ability, (c) the scope (scope) and sequences need to be arranged so that it is systematic and clearly, and (d) time and equipment are also considered. (2) The application of learning methods in SMA Adabiah Padang has implemented the learning methods in very good categories because it has used many methods in the learning process such as the question and answer method, lectures, assignments, discussions, and demonstrations. (3) The evaluation of learning in SMA Adabiah Padang is good. The teacher evaluates speaking skills with the appropriate aspects, namely intonation, pronunciation, fluency, expression, appearance, and gesture. Kata Kunci: Pelaksanaan, Keterampilan, Berbicara, Mata pelajaran bahasa Indonesia